Spiritual Well-Being and Related Factors in Iranian Medical Students - Salehi, Alireza (Journal of spirituality in mental health, 2017)
The purpose of this research is to explore the association between the level of spiritual well-being score (SWBS) and related factors. The standard spiritual well-being questionnaire used in this study was customized to Persian. The statistical evaluation of the data was carried out using chi square, t-tests, ANOVA, multivariate linear regression analysis, and meta-analysis. SWBS is high in univariate analysis in female versus male, married versus unmarried students without history of mental disorder and who more associated with the major. This association remained significant in multivariate linear regression in relation to the major and history of mental disorder.